The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1123/ijsnem.2014-0178
|View full text |Cite
|
Sign up to set email alerts
|

Ingesting Isomaltulose Versus Fructose-Maltodextrin During Prolonged Moderate-Heavy Exercise Increases Fat Oxidation but Impairs Gastrointestinal Comfort and Cycling Performance

Abstract: Certain commercial carbohydrate replacement products include slowly absorbed carbohydrates such as isomaltulose. Few studies have investigated the metabolic effects of ingesting isomaltulose during exercise and none have evaluated exercise performance and gastrointestinal comfort. Nine male cyclists participated postprandially during three trials of 2-h steady-state (S-S) exercise (60%Wmax) followed by a 16 km time trial (TT) while ingesting 63 g·h-1 of either, 0.8:1 fructose: maltodextrin (F:M) or isomaltulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
3
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 34 publications
4
40
3
5
Order By: Relevance
“…However, the GI of ingested CHO has a distinct influence on important metabolic processes under both resting or pre-exercise conditions and during exercise. It has been previously demonstrated that the course of blood glucose and insulin levels following ingestion of low GI CHO favored a higher level of free fatty acids during exercise and was associated with enhanced fat oxidation and improved blood glucose homeostasis [ 6 , 7 , 24 , 25 , 26 , 27 ]. During submaximal endurance exercise, the maintenance of higher fat oxidation leads to a sparing of glycogen in muscles and particularly in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…However, the GI of ingested CHO has a distinct influence on important metabolic processes under both resting or pre-exercise conditions and during exercise. It has been previously demonstrated that the course of blood glucose and insulin levels following ingestion of low GI CHO favored a higher level of free fatty acids during exercise and was associated with enhanced fat oxidation and improved blood glucose homeostasis [ 6 , 7 , 24 , 25 , 26 , 27 ]. During submaximal endurance exercise, the maintenance of higher fat oxidation leads to a sparing of glycogen in muscles and particularly in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Isomaltulose thereby produces a lower glycaemic and insulinaemic response following ingestion, and suppresses fat oxidation to a lesser extent than sucrose [31]. However, presumably due to this slow rate of digestion and absorption, isomaltulose exacerbates gastrointestinal distress when consumed in large amounts during exercise [32]. …”
Section: Dietary Carbohydrates For Sport Nutritionmentioning
confidence: 99%
“…This effect is attributed to the lowering effect of isomaltulose on blood glucose and insulin levels compared to readily available high-glycemic carbohydrates. The higher fat oxidation in energy metabolism has been demonstrated during various physical activities in studies including healthy and overweight-to-obese adults, diabetic individuals, as well as trained athletes [24,31,32,33,34,35,36] (see Figure 2). …”
Section: Sports Nutrition and Cognitive Performancementioning
confidence: 99%
“…These results were explained by the slow-release and low-glycemic properties of isomaltulose which allowed reliance upon more fat oxidation and spare glycogen during the initial exercise period [33]. A small trial with several shortcomings, however, comparing isomaltulose versus a fructose-maltodextrin blend in nine cyclists could not confirm these effects [35]. A double-blinded, counterbalanced, within-group study in resistance-trained men suggests that the addition of isomaltulose as a slow-release carbohydrate and β-hydroxy-β-methylbutyrate to a recovery protein drink may enhance recovery from resistance exercise.…”
Section: Sports Nutrition and Cognitive Performancementioning
confidence: 99%